Implementasi PERMENKES Nomor 18 Tahun 2020 Terhadap Pengolahan Limbah Medis Rumah Sakit - Afiyah, Lisa Lamusul (Universitas Ekasakti, 2023)
The management of B3 waste resulting from hospital activities that are not in accordance with statutory regulations will certainly cause environmental pollution. One of the regulations related to the application of waste is contained in the Republic of Indonesia Minister of Health Regulation Number 18 of 2020, namely regarding the management of medical waste in area-based health service facilities. In its implementation, there are many cases where medical waste is not managed according to the procedures regulated by law. The normative legal research method concerns related laws. The results of implementation research from the implementation of Minister of Health Regulation No. 18 of 2020 show that medical waste processing in hospitals is still not being implemented well, as evidenced by the findings of 44 cases that occurred after the legalization of this regulation from 2020 to November 2023, the main factor causing B3 waste pollution in managing medical waste is not following procedures in terms of transporting and sorting medical waste. The solution to overcome obstacles is to be firm in both central and regional governments regarding the implementation of articles 9 and 12 of Minister of Health Regulation No. 18 of 2020.